Cognitive and Central Vestibular Functions Correlate in People With Multiple Sclerosis. (November 2021) - Cochrane, Graham D.; Christy, Jennifer B.; Sandroff, Brian M.; Motl, Robert W.
Background. Cognitive impairment is common, but poorly managed in people with multiple sclerosis (MS). Balance has been correlated with cognition in people with MS, potentially through shared utilization of central sensory integration pathways. Objective. This study characterized the relationship between central vestibular integration and cognition in people with MS through measurement of several clinical vestibular functions requiring central sensory integration and multiple cognitive domains. Methods. Forty people with MS and 20 controls completed a battery of vestibular and cognitive examinations targeting different central vestibular integration measures and different domains of cognition, respectively. Performance on these measures was compared between people with MS and controls, and then correlational analyses were undertaken between the vestibular and cognitive measures in the MS sample. Results. People with MS performed worse than controls on all vestibular and cognitive measures. There were consistent correlations between vestibular and cognitive measures in the MS sample. Factor analysis of vestibular functions yielded a single factor hypothesized to represent central vestibular integration that demonstrated a significant relationship with a composite cognitive measure in people with MS. Discussion. Our results suggest that vestibular and cognitive dysfunction may both arise from central sensory processing pathways in people with MS. This connection could be targeted through vestibular rehabilitation techniques that improve central sensory processing and both balance and cognition in people with MS.